2021
DOI: 10.4300/jgme-d-20-01259.1
|View full text |Cite
|
Sign up to set email alerts
|

Factors Influencing the Entrustment of Resident Operative Autonomy: Comparing Perceptions of General Surgery Residents and Attending Surgeons

Abstract: Background General surgery residents may be underprepared for practice, due in part to declining operative autonomy during training. The factors that influence entrustment of autonomy in the operating room are unclear. Objective To identify and compare the factors that residents and faculty consider influential in entrustment of operative autonomy. Methods An… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 31 publications
(34 reference statements)
2
4
0
Order By: Relevance
“…In the operating room, attending surgeons' expert subjective judgment guides their intraoperative teaching actions, and the objective patterns of resident ICT are a result of attending surgeons’ subjective assessment and judgement. Our study suggests that resident opportunities for autonomy in RC, RIH, and RVH are influenced by resident seniority level, surgeon work experience, and procedure type, which is consist with literature [ [14] , [15] , [16] , [17] ] and supported by the situated learning theory. Interviews with surgeons revealed that resident training year and experience, and the attending surgeons perceived operative time pressure, are the major influences on granting resident ICT; these are similar factors to those found in non-RAS operations reported in literature [ 14 , 16 , 23 ].…”
Section: Discussionsupporting
confidence: 77%
See 2 more Smart Citations
“…In the operating room, attending surgeons' expert subjective judgment guides their intraoperative teaching actions, and the objective patterns of resident ICT are a result of attending surgeons’ subjective assessment and judgement. Our study suggests that resident opportunities for autonomy in RC, RIH, and RVH are influenced by resident seniority level, surgeon work experience, and procedure type, which is consist with literature [ [14] , [15] , [16] , [17] ] and supported by the situated learning theory. Interviews with surgeons revealed that resident training year and experience, and the attending surgeons perceived operative time pressure, are the major influences on granting resident ICT; these are similar factors to those found in non-RAS operations reported in literature [ 14 , 16 , 23 ].…”
Section: Discussionsupporting
confidence: 77%
“…Our study suggests that resident opportunities for autonomy in RC, RIH, and RVH are influenced by resident seniority level, surgeon work experience, and procedure type, which is consist with literature [ [14] , [15] , [16] , [17] ] and supported by the situated learning theory. Interviews with surgeons revealed that resident training year and experience, and the attending surgeons perceived operative time pressure, are the major influences on granting resident ICT; these are similar factors to those found in non-RAS operations reported in literature [ 14 , 16 , 23 ]. We thus encourage residency programs to provide faculty development for attending surgeons to improve their intraoperative teaching and performance evaluation skills for working with residents performing RAS in aid of robotic surgical workforce training and patient safety.…”
Section: Discussionsupporting
confidence: 77%
See 1 more Smart Citation
“…In general surgery and in many other surgical specialties, there is a high level of concern that duty-hour restrictions, the proliferation of subspecialty fellowships at institutions (which are perceived to crowd out residents from the operating room), and an increased focus on nonclinical electives and research time has resulted in decreased resident autonomy and decreased preparedness for independent practice as graduating residents. [11][12][13][14][15][16][17] One solution to this problem in these specialties has been the institution of formal resident-run clinics that focus on minor procedures. 18,19 Studies show that these clinics are safe for patients and effective as training tools for residents.…”
Section: Discussionmentioning
confidence: 99%
“…Convincing evidence for student learning in all domains of competence is being increasingly demanded by educators, accrediting bodies, and stakeholders alike ( 10 ). In medical education, a recent study compared competencies measured using Likert type scales to those using entrustment scales ( 11 ) and national studies are being conducted to compare milestone ratings in resident training programs with national licensing examination scoring ( 12 ). Veterinary specific examples are more limited to date however there has been demonstration of strong validity evidence for a programmatic assessment approach ( 13 ).…”
Section: Introductionmentioning
confidence: 99%